PENGGUNAAN MEDIA BLOG DENGAN PENDEKATAN KONSTRUKTIVISME UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA - Lia Herliana (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2017)
The instructional problem in writing was students’ low skills, especially in expository writing. Even, low writing skills was also influenced by students’ motivation and conventional learning media. Thus, it was necessary to use different instructional media so that students’ writing ability and motivation improved . It was an action research . It used verbal and nonverbal data analysis . Verbal data were in the form of questionnaires, interviews, and questions while the nonverbal data were in the form of an observation sheet containing students’ learning interest, students’ determination of learning, etc . The learning evaluation was taken through tests and the other . The result showed that students’ learning outcomes increased from cycle 1 with an average score of 64.05 in sufficient category to cycle 2 with an average score of 78.05 in good category. The student skill improvement in expository writing increased 14.00. In cycle 1, the level of students’ participation in the activity was 75% and in cycle 2 students’ participation was 96 .43% . The evaluation of teacher performance observation during the learning process in cycle 1 was 65% and in cycle 2 was 95%. In conclusion, the expository writing skills and students’ motivation increased in the learning using blog and constructivism approach .